Transformasi Ekonomi Syari’ah Dalam Ekonomi Kerakyatan Di Indonesia - Aufa Rizka Azzumi; Miswanto Miswanto; Abdul Basit (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2022)
If We observe Islamic Economics, something economy that underlies its implementation of character balanced more defend in people's Economy as well as digitization. Islamic economics is the Economy that makes the whole safe as well as no screwup area around him. Progress economy as well as field sharia business in Indonesia or in this country which continues to drove fast, have satisfaction on the desire of Islamic HR. Progress Indonesia's Economy experienced significant progress, signaled by progress field effort agency Islamic finance such as Islamic Commercial Banks, Bank Muamalat Indonesia, Bank Syariah Mandiri, Bank Syariah Mega Indonesia, are part from sharia efforts of conventional banks, BPRS, BMT, Takaful, and others, are reviewed from whole the assets or total distributed financing. Stated in the review above, economics in Islam must share opportunity widely in each executor's business. Not only, Therefore, Islamic economics also emphasizes four characteristics, including Unity (Unity), Balance (equilibrium), independence (free will), and responsibility (responsibility). Man, as the messenger (Khalifah) of God on earth no, can become a character human individualistic cause all (wealth) contained in nature is the right of Allah alone, as well as people who believe in their hearts. Because that is what Islamic Economics does, leads to needing Public small or always hold aspect development economy nationality is how the general public is actively raising his income.